2013
DOI: 10.1007/s11845-013-0977-z
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic cranial irradiation in small cell lung cancer: a single institution experience

Abstract: Our study demonstrated a low incidence of symptomatic brain metastases and favourable median PFS and OS in the patients that received PCI, when compared to published phase III data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Analysis of 34 patient cases without cranial metastasis who received prophylactic cranial irradiation, a SCLC treatment (4,19), following chemotherapy demonstrated that low-NLR patients who received prophylactic cranial irradiation (n=6) had a longer PFS than those who did not (n=28; 9.00±1.16 vs. 5.00±0.60 months; P= 0.039; Fig. 3E).…”
Section: Association Between Nlr Cranial Radiotherapy and Pfsmentioning
confidence: 99%
“…Analysis of 34 patient cases without cranial metastasis who received prophylactic cranial irradiation, a SCLC treatment (4,19), following chemotherapy demonstrated that low-NLR patients who received prophylactic cranial irradiation (n=6) had a longer PFS than those who did not (n=28; 9.00±1.16 vs. 5.00±0.60 months; P= 0.039; Fig. 3E).…”
Section: Association Between Nlr Cranial Radiotherapy and Pfsmentioning
confidence: 99%
“…Since PCI not only produces a reduction in BM incidence but also provides an improvement in survival 5 , published guidelines always recommend PCI for both LD and ED patients who have a good response to initial treatment 6 7 . Yet, some patients still cannot avoid developing BM despite they have adopted PCI 4 8 9 10 . It remains unestablished that what factors cause some patients develop BM after PCI.…”
mentioning
confidence: 99%
“…Secondly, brain metastasis is one of the most important causes of treatment failure in patients with SCLC. Several randomized studies showed that PCI could reduce the rate of brain metastases in patients with SCLC who achieved CR . In these studies, the rates of brain metastases were from 42.0% to 67.1% in the patients who did not experience PCI and 11.0% to 40.0% in the patients who experienced PCI.…”
Section: Discussionmentioning
confidence: 99%